2016
DOI: 10.4238/gmr.15036683
|View full text |Cite
|
Sign up to set email alerts
|

Validation of associations between ESR1 variants and breast cancer risk in Chinese cohorts

Abstract: ABSTRACT. Estrogen receptor-a (ER) protein plays a key role in breast carcinogenesis, and common genetic variants in the corresponding gene locus have been associated with breast cancer risk in different populations. Here, we analyzed estrogen receptor 1 (ESR1) associations in two hospital-based studies of patients from the south of China. Three single-nucleotide polymorphisms (SNPs; rs3757318, rs2046210, and rs3734805) in ESR1 were selected from previous genome-wide association study results and were genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 14 publications
0
1
0
Order By: Relevance
“…Elevated estrogen levels have been shown to be associated with an increased risk of breast cancer in previous studies [50]. It is hypothesized that rs2046210 together with ESR1 may play an essential role in estrogen-dependent mammary epithelial proliferation, which is associated with increased mammographic density and subsequent risk to BC [51][52][53]. Other loci, such as rs10474352 [54], rs6788895 [55], rs7107217 et al [56], were also identified in previous studies in HCW and have the potential to be a predictive variable to asses the risk of BC.…”
Section: Discussionmentioning
confidence: 99%
“…Elevated estrogen levels have been shown to be associated with an increased risk of breast cancer in previous studies [50]. It is hypothesized that rs2046210 together with ESR1 may play an essential role in estrogen-dependent mammary epithelial proliferation, which is associated with increased mammographic density and subsequent risk to BC [51][52][53]. Other loci, such as rs10474352 [54], rs6788895 [55], rs7107217 et al [56], were also identified in previous studies in HCW and have the potential to be a predictive variable to asses the risk of BC.…”
Section: Discussionmentioning
confidence: 99%